Severe Burn-Induced Intestinal Epithelial Barrier Dysfunction Is Associated With Endoplasmic Reticulum Stress and Autophagy in Mice - Huang, Yalan; Feng, Yanhai; Wang, Yu; Wang, Pei; Wang, Fengjun; Ren, Hui (Frontiers in Physiology, 2018)
The disruption of intestinal barrier plays a vital role in the pathophysiological changes after severe burn injury, however the underlying mechanisms are poorly understood. Severe burn causes the disruption of intestinal tight junction (TJ) barrier. Previous studies have shown that endoplasmic reticulum (ER) stress and autophagy are closely associated with the impairment of intestinal mucosa. Thus, we hypothesize that ER stress and autophagy are likely involved in burn injury-induced intestinal epithelial barrier dysfunction. Mice received a 30% total body surface area (TBSA) full-thickness burn, and were sacrificed at 0,1, 2, 6, 12 and 24 h postburn. The results showed that intestinal permeability was increased significantly after burn injury, accompanied by the damage of mucosa and the alteration of TJ proteins. Severe burn induced ER stress, as indicated by increased intraluminal chaperone binding protein (BIP), CCAAT/enhancer-binding protein homologous protein (CHOP) and inositol-requiring enzyme 1(IRE1)/X-box binding protein 1 splicing (XBP1). Autophagy was activated after burn injury, as evidenced by the increase of autophagy related protein 5(ATG5), Beclin 1 and LC3II/LC3I ratio and the decrease of p62. Besides, the number of autophagosomes was also increased after burn injury. The levels of p-PI3K(Ser191), p-PI3K(Ser262), p-AKT(Ser473) and p-mTOR were decreased postburn, suggesting that autophagy-related PI3K/AKT/mTOR pathway is involved in the intestinal epithelial barrier dysfunction following severe burn. In summary, severe burn injury induces the ER stress and autophagy in intestinal epithelia, leading to the disruption of intestinal barrier.